2011
DOI: 10.1128/aac.00304-11
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Species and Azole Resistance in the Aspergillus niger Complex

Abstract: Aspergillus niger is a common clinical isolate. Multiple species comprise the Aspergillus section Nigri and are separable using sequence data. The antifungal susceptibility of these cryptic species is not known. We determined the azole MICs of 50 black aspergilli, 45 from clinical specimens, using modified EUCAST (mEUCAST) and Etest methods. Phylogenetic trees were prepared using the internal transcribed spacer, beta-tubulin, and calmodulin sequences to identify strains to species level and the results were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 50 publications
12
88
0
7
Order By: Relevance
“…In recent years, sequence-based molecular methods have been used successfully for species identification in this group, particularly methods using the calmodulin gene, which can distinguish all species within section Nigri (4-6). Molecular studies indicated that several species in addition to A. niger were able to cause human infections; different regions had different species of pathogenic black Aspergillus, and A. niger and Aspergillus tubingensis were the most frequently identified pathogens in previous studies (2,(7)(8)(9)(10)(11)(12)(13)(14). Additionally, it is worth noting in a clinical context that azoles exhibited different activity against the two species and that isolates from different geographical regions exhibited remarkable differences in susceptibility to azoles and amphotericin B (1-13, 15).…”
Section: Molecular Identification and In Vitro Antifungal Susceptibilmentioning
confidence: 99%
“…In recent years, sequence-based molecular methods have been used successfully for species identification in this group, particularly methods using the calmodulin gene, which can distinguish all species within section Nigri (4-6). Molecular studies indicated that several species in addition to A. niger were able to cause human infections; different regions had different species of pathogenic black Aspergillus, and A. niger and Aspergillus tubingensis were the most frequently identified pathogens in previous studies (2,(7)(8)(9)(10)(11)(12)(13)(14). Additionally, it is worth noting in a clinical context that azoles exhibited different activity against the two species and that isolates from different geographical regions exhibited remarkable differences in susceptibility to azoles and amphotericin B (1-13, 15).…”
Section: Molecular Identification and In Vitro Antifungal Susceptibilmentioning
confidence: 99%
“…Amongst the species of the section Nigri, Aspergillus niger has been reported as the most frequent aetiological agent of otomycosis (Kaya & Kiraz, 2007). Nevertheless, the clinical implications of other species are rarely reported and they are generally misidentified as A. niger (Howard et al, 2011). Identification of clinical isolates of Aspergillus to the species level is important because different species may have dissimilar susceptibilities to antifungal drugs.…”
Section: Black Aspergillus Species Isolated From Clinical and Environmentioning
confidence: 99%
“…The L98H, M220 and Tandem Repeat were not detected at all in Aspergillus niger isolates and the resistance in A. niger may be due to other factors [6]. Meanwhile the resistance isolates which do not show any gene expression or L98H, M220 and TR mutation could be due to presence of other mutations such as F46Y, G89G, M172V, N248 T, D255E, L358L, E427K, C454C, L358L or efflux pump mechanism [14].…”
Section: Discussionmentioning
confidence: 99%
“…However it was not possible to amplify the other isolates with the primer pair employed. This is because A. niger is a species complex consisting of numerous different strains [14] and several other primer pairs would have to be used in order to amplify the other isolates [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%